Stop suffering! economic downturns and pentecostal upsurge - Costa, Francisco Junqueira Moreira da (2019)
Economic distress and impoverishment have been generally associated with the rise of religiosity and religious fundamentalism in several contexts, even within developed countries.1 Expectations that religiosity would fade away in increasingly modern societies have given way to a renewed recognition of the influence of religion on the world’s social and political landscape. As shown by Inglehart and Norris (2004), the world has more people with traditional religious views than ever before, particularly in impoverished contexts. The growth of ethno-religious conflicts and of fundamentalist movements in Muslim and Christian communities are some of the most prominent indicators of the vitality of religions in the world today.